Valorization of Municipal Solid Waste Using Hydrothermal Carbonization and Gasification: A Review - Cubillos-Montecino, F; Diaz-Robles, L; Espinoza-Perez, A; Vallejo-Gallardo, F; Espinoza-Perez, L (Italian Association of Chemical Engineering - AIDIC, 2020)
In developing countries, there is a relevant problem related to air pollution caused by the indiscriminate use of residual biomass and the disposal of Municipal Solid Waste. Currently, various technologies (biological, thermal, thermochemical, among others) are available to valorize them. This review shows a current summary of two technologies: hydrothermal carbonization and gasification. The first one has been considered as a Waste to Energy technology capable of providing a solid, that can be used as a fuel, with higher calorific value and lower moisture and ash content than raw residual biomass. On the other hand, gasification generates syngas used as fuel or in the generation of electricity. During the last decade, most of the studies focused on hydrothermal carbonization of Municipal Solid Waste in contrast to gasification. However, the integration of those technologies has not even had the same interest. This study analyzed in-depth the product characteristics and the associated costs for both processes, including from transportation to obtaining the final product. Both promising Waste to Energy alternatives can result in Municipal Solid Waste disposal cost savings and environmental impact reductions. Nevertheless, research combining technologies must be enhanced in order to develop sustainable systems. © 2020 Italian Association of Chemical Engineering - AIDIC. All rights reserved.